Increasing the Performance of {[(1-x-y) LiCo0.3Cu0.7] (Al and Mg doped)] O2}, xLi2MnO3, yLiCoO2 Composites as Cathode Material in Lithium-Ion Battery: Synthesis and Characterization - Shahriari, Sara; Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2023)
Twenty-eight samples of {[(1-x-y) LiCo0.3Cu0.7](Al and Mg doped)]O2}, xLi2MnO3, and yLiCoO2 composites were synthesized using the sol–gel method. Stoichiometric weights of LiNO3, Mn(Ac)2⋅4H2O, Co(Ac)2⋅4H2O, Al(NO3)3.H2o, Mg(NO3)2⋅6H2O, and Cu(NO3)2.H2O for the preparation of these samples were applied. From this work, we confirmed the high performance of two samples, namely, Sample 18, including Al doped with structure “Li1.5Cu0.117Co0.366Al0.017Mn0.5O2” and Sample 17, including Mg doped with structure “Li1.667Cu0.1Mg0.017Co0.217Mn0.667O2”, compared with other compositions. Evidently, the used weight of cobalt in these two samples were lower compared with LiCoO2, resulting in advantages in the viewpoint of cost and toxicity problems. Charge and discharge characteristics of the mentioned cathode materials were investigated by performing cycle tests in the range of 2.2–4.5 V. These types of systems can help to reduce the disadvantages of cobalt arising from its high cost and toxic properties. Our results confirmed that the performance of such systems is similar to that of pure LiCoO2 cathode material, or greater in some cases. The biggest disadvantages of LiCoO2 are its cost and toxic properties, typically making it cost around five times more to manufacture than when using copper.
Keywords: cathode materials; Mg doping; lithium-ion batteries; Al doping; Article; LiCoO2; TJ1-1570; lithium-ion batteries; Al doping; Mg doping; cathode materials; LiCoO2; Mechanical engineering and machinery; 7. Clean energy